Antiviral, Antiprotozoal, Antimalarial and Insecticidal Activities Ofocimum Gratissimum L. - Pandey, Sandeep; Singh, Satyendra Kumar; Kumar, Neetesh; Manjhi, Ravishanker (Asian Journal of Pharmaceutical Research and Development, 2017)
Ocimum gratissimum has been used in traditional medicine for curing various ailments in tropical countries. The plant with unique bioactive compounds possesses a significant medicinal value. Among numerous curative properties the plant shows strong inhibition against human viruses and parasitic protozoans. The presence of eugenol makes it a safe mosquito repellent and anti-malarial agent. Moreover, the plant causes mortality of agricultural insects in both store seed and field crops. The researches have also proved the inhibitory action of plants against various plants and human nematodes harboring alimentary canal. Thus, there is a need to explore the potentiality of this plant to discover biological drug formulation with relevant action against plant and animal microbes, malaria parasites and nematodes. This systematic review presents the antiviral, antiprotozoal, antimalarial, insecticides and nematicidal activities of the plant for developing a standard therapeutic system.